A toughened polymer / molecular sieve blend injection molding desiccant and its preparation method and application
Patent Information
- Application Number
- CN202610988078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-16
AI Technical Summary
然而,此类纤维膜材料为无纺布状,力学强度低,无法制成具有规定形状和足够刚性的独立结构件,难以通过弹性形变实现过盈安装,且纤维膜在反复拆装和挤压中易破损,不适用于电池包、医疗器械等需要定期拆卸维护的场景
[0049](1) The toughened desiccant product of the present invention has a flexural modulus that is 30% to 70% lower than that of the same thermoplastic polymer/molecular sieve injection molding system without flexible polymer, and a breaking elongation greater than 20%. It can produce visible elastic bending and compression deformation under external force, and basically recovers its original shape after the external force is removed. It can be repeatedly bent to 90° around a round rod with a diameter of 10 mm without cracks appearing on the surface.
Smart Images

Figure CN122912818A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of desiccant materials technology, specifically relating to a toughened polymer / molecular sieve blend injection molding desiccant (flexible desiccant) and its preparation method and application. Background Technology
[0002] In enclosed or semi-enclosed spaces such as power battery packs, outdoor electronic devices, medical equipment, precision instruments, and medicine bottles, diurnal temperature variations or changes in ambient humidity can easily lead to condensation, causing problems such as short circuits in electronic components, corrosion of metal parts, failure of biological reagents, and deterioration of medicines due to moisture. To maintain a low-humidity environment, desiccant packs are usually placed inside the equipment.
[0003] Existing desiccants are mostly molecular sieve particles or silica gel particles filled in non-woven bags or rigid plastic boxes, with a fixed shape that cannot fit into complex, narrow, or irregular gaps. In applications such as endoscope storage tubes for medical devices, curved interlayers in portable diagnostic instruments, and the inner cavities of medicine bottle caps, traditional desiccant bags / boxes are completely unsuitable for installation, and the desiccant particles can easily leak and contaminate the instruments or medicines. There are also solutions that coat molecular sieve powder with adhesives onto flexible substrates, but the moisture absorption capacity is limited by the thickness of the adhesive layer, and long-term use carries the risk of powder shedding and delamination, which is unacceptable in the medical and pharmaceutical fields due to the high cleanliness requirements.
[0004] Chinese Patent CN101229808A (Application No. CN200710135007.4, Invention Title: A Polymer-Based Moisture-Absorbing Material and Its Preparation Method) discloses a polymer-based moisture-absorbing material and its preparation method. The moisture-absorbing material comprises 30%–80% desiccant, 10%–35% carrier resin, 3%–15% compatibilizer, 1%–5% lubricant, and 3%–15% moisture-absorbing aid. The desiccant is selected from at least one of clay desiccant, metal oxide desiccant, inorganic salt desiccant, molecular sieve, silica gel, and activated carbon. The carrier resin is a thermoplastic. The moisture-absorbing aid is a hydrophilic fiber with a length ranging from 0.5 to 5 mm. This solution achieves "dust-free peeling" through the compatibilizer and can be processed into different shapes such as films, solids, or elastomers through injection molding, extrusion, and compression molding processes. However, while the patent mentions the possibility of an "elastomer" form, it achieves elasticity through a composite of hydrophilic fibers and carrier resin, without addressing the technical approach of introducing a flexible polymer dispersion phase into the system for toughening modification. More importantly, the patent only focuses on dust-free peeling under static conditions, neglecting the desiccant's resistance to powder shedding during dynamic elastic deformation processes such as repeated bending and compression. This performance is precisely crucial for achieving interference fit of the desiccant through elastic deformation in narrow, irregular, and confined spaces.
[0005] While blending thermoplastic resins with flexible polymers for toughening is common in the field of polymer modification, it cannot be directly applied to highly filled molecular sieve desiccant systems. This is because: (1) when the molecular sieve content reaches 50%, the polymer matrix is already in an "overloaded" state. Introducing flexible polymers as a second phase will face multiple interfacial compatibility issues between the thermoplastic matrix, the flexible phase, and the molecular sieve; (2) improper dispersion of flexible polymers (especially non-polar POE, SEBS, etc.) can lead to uneven distribution in the continuous matrix, forming local enrichment and depletion zones, thus affecting the internal structure of the product. The mechanical properties exhibit significant non-uniformity; the enriched areas are too soft and the depleted areas are too rigid and brittle. When subjected to bending or compression deformation, the stress cannot be uniformly transmitted and dissipated throughout the entire product, resulting in deformation concentration in local weak areas, ultimately manifesting as insufficient overall elastic deformation capacity or even local fracture; (3) To maintain interfacial bonding and prevent powder shedding under repeated elastic deformation conditions, the interface must maintain good bonding strength throughout the repeated deformation process, which is far higher than the requirements for interfacial bonding in static use scenarios; (4) Introducing a flexible phase into a high-filling system will cause the melt viscosity to rise sharply and the processing window to narrow significantly. Solving the above technical problems requires a systematic redesign of the formulation and process based on the functional requirements of the desiccant, rather than simply applying conventional toughening technologies for polymer plastics.
[0006] In practical engineering and medical applications, many confined spaces often lack regular assembly interfaces. Examples include irregular gaps between internal modules and the casing of battery packs, recesses in irregularly shaped covers of electronic instruments, curved guide grooves in endoscope storage cabinets in medical devices, curved interlayers in portable diagnostic instruments, and narrow annular grooves in the inner cavity of medicine bottle caps. These scenarios not only present limited space but also often require the desiccant to undergo elastic bending, compression, or extrusion deformation during installation to conform to the piping routing or be interference-fitted. Using high-rigidity injection-molded desiccants can lead to difficulty in insertion due to the inability to produce recoverable elastic deformation, or even breakage due to stress concentration after forced installation. Using purely flexible elastomer desiccants results in low strength, poor shape retention, and inability to withstand repeated operations or thermal activation. Furthermore, purely elastomer materials may pose compatibility risks in environments where they indirectly contact pharmaceuticals due to the migration of excipients.
[0007] Existing technologies also include methods for loading molecular sieves onto electrospun nanofiber membranes. For example, Chinese patent application CN120591909A (application number CN202510523070.3, invention title: A melt electrospun polymer / molecular sieve blend composite fiber and its preparation method and application) discloses a melt electrospun polymer / molecular sieve blend composite fiber, the raw materials of which, by weight, include 25-90 parts of thermoplastic polymer matrix, 5-75 parts of molecular sieve, 1-10 parts of compatibilizer, and 0-5 parts of conductive additive. This method improves the functional accessibility of molecular sieves through the high specific surface area of ultrafine fibers and constructs a hierarchical porous structure to significantly improve adsorption efficiency. However, such fiber membrane materials are non-woven fabrics with low mechanical strength, making it impossible to manufacture independent structural components with a specified shape and sufficient rigidity. It is difficult to achieve interference fit through elastic deformation, and the fiber membrane is easily damaged during repeated disassembly and compression, making it unsuitable for scenarios such as battery packs and medical devices that require regular disassembly and maintenance.
[0008] Therefore, there is an urgent need for a desiccant product that retains the advantages of injection molding, such as dimensional designability, high moisture absorption, and no powder shedding, while also possessing moderate elastic deformation capability. This would meet the dual requirements of "precision injection molding" and "bending and extrusion installation," and would be particularly suitable for applications in new energy, medical devices, and pharmaceutical packaging where cleanliness, deformation adaptability, and reliability are critical. Summary of the Invention
[0009] To address the shortcomings and deficiencies of existing technologies, the primary objective of this invention is to provide a toughened polymer / molecular sieve blend injection molding desiccant.
[0010] Another object of the present invention is to provide a method for preparing the above-mentioned toughened polymer / molecular sieve blend injection molding desiccant.
[0011] Another object of the present invention is to provide the application of the above-mentioned toughened polymer / molecular sieve blend injection molding desiccant.
[0012] The objective of this invention is achieved through the following technical solution:
[0013] A toughened polymer / molecular sieve blend injection molding desiccant is prepared from the following raw materials: 20-45 parts by weight of thermoplastic polymer, 50-78 parts by weight of molecular sieve, 5-25 parts by weight of flexible polymer, 0.5-5 parts by weight of compatibilizer, 0.2-3 parts by weight of processing aid, and 0-25 parts by weight of auxiliary water-absorbing material; wherein the compatibilizer is at least one selected from maleic anhydride grafted polymer, silane coupling agent, titanate coupling agent, and aluminate coupling agent. In the toughened polymer / molecular sieve blend injection molding desiccant, the thermoplastic polymer forms a continuous phase matrix, and the flexible polymer is uniformly dispersed in the continuous phase under the action of the compatibilizer for toughening modification.
[0014] Furthermore, the thermoplastic polymer is selected from at least one of polyolefins, polyamides, thermoplastic polyurethanes, polycarbonates, and polyoxymethylene. Thermoplastic polymers are chosen as the main continuous phase because they possess excellent heat resistance (remaining undeformed after repeated activation at 80–120°C), shape retention due to high crystallinity, and good injection molding precision. The continuous thermoplastic polymer phase ensures the dimensional stability of the product during high-temperature activation and regeneration.
[0015] In a more preferred embodiment, the polyolefin is preferably at least one of polypropylene (PP), high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), ethylene-vinyl acetate copolymer (EVA), and ethylene-ethyl acrylate copolymer (EEA); and the polyamide is preferably at least one of polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, and polyamide 1010.
[0016] Furthermore, the flexible polymer is selected from at least one of styrene-based block copolymers, polyolefin elastomers (POE), and thermoplastic polyurethane elastomers (TPU). Thanks to the bridging effect of the compatibilizer, the flexible polymer can be uniformly dispersed in the continuous phase of the thermoplastic polymer at a small size, thus imparting bendability and elastic recovery to the product.
[0017] Furthermore, the weight ratio of the continuous phase (thermoplastic polymer) to the dispersed phase (flexible polymer) is (50-90):(10-50), preferably (60-80):(20-40). If the content of flexible polymer is less than 10% (relative to the total amount of continuous and dispersed phases), the toughening effect is not significant, and the product still exhibits brittle fracture or low elongation. If the content of flexible polymer is greater than 50% (relative to the total amount of continuous and dispersed phases), the dispersed phase may undergo phase inversion, the matrix strength decreases significantly, the product loses the self-supporting ability and shape retention that injection molded parts should have, and it is prone to heat deformation when activated above 80°C.
[0018] In a more preferred embodiment, the styrene-based block copolymer is preferably at least one of styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), and styrene-isobutylene-styrene block copolymer (SIBS).
[0019] SEBS is a hydrogenated product of SBS, possessing excellent aging resistance, mechanical properties, and processing ease, and is widely used in medical devices, automotive parts, and consumer electronics. SBS (styrene-butadiene-styrene block copolymer) is the unhydrogenated variety, with polybutadiene as the soft segment. SIS (styrene-isoprene-styrene block copolymer) and hydrogenated SIS (SEPS) also belong to the styrene-based thermoplastic elastomer family. SEEPS (styrene-ethylene-ethylene-propylene-styrene block copolymer) and SIBS (styrene-isobutylene-styrene block copolymer) are newer styrene-based block copolymer varieties developed in recent years, exhibiting superior heat resistance and low gas permeability. POE is a thermoplastic elastomer synthesized in situ from ethylene and octene or butene using a metallocene catalyst, and is divided into ethylene-butene copolymers and ethylene-octene copolymers. POE has a narrow molecular weight distribution, low density and crystallinity, exhibiting high elongation at break, high elasticity, excellent impact resistance, and low-temperature resistance. POE has good compatibility with polypropylene, low processing temperature, and good dispersibility. It easily yields small dispersed phase particle sizes and narrow particle size distributions within the matrix, thus significantly enhancing the toughening effect of polypropylene. TPU is a block copolymer formed by the reaction of diisocyanate and polyol. Hard segments provide strength, while soft segments impart elasticity. TPU can be classified into polyester type and polyether type according to its molecular structure.
[0020] Furthermore, the molecular sieve is selected from at least one of 3A, 4A, 5A, 13X, Y-type, and ZSM-5 type molecular sieves, with a specific surface area ≥ 500 m². 2 / g, pore size 0.3–1.2 nm, particle size D 1–10 μm (preferably 1–8 μm). Fine particles facilitate the formation of continuous adsorption channels by overlapping within the matrix; however, excessively large particles reduce the moisture absorption effect. When the molecular sieve addition amount is less than 50 parts by weight, the water absorption capacity is insufficient and it is difficult to form continuous adsorption channels; when the molecular sieve addition amount is greater than 78 parts by weight, the melt viscosity increases sharply, making processing difficult, and the mechanical strength of the product, especially the elongation at break, deteriorates significantly, making it difficult to meet the requirements for elastic deformation installation.
[0021] Furthermore, the grafting rate of the maleic anhydride grafted polymer is 0.8% to 2%.
[0022] Furthermore, the compatibilizer is at least one of maleic anhydride-grafted polypropylene (PP-g-MAH), maleic anhydride-grafted polyethylene (PE-g-MAH), maleic anhydride-grafted SEBS (SEBS-g-MAH), maleic anhydride-grafted POE (POE-g-MAH), silane coupling agents, titanate coupling agents, and aluminate coupling agents. The anhydride groups or coupling agent functional groups of the compatibilizer can chemically bond or strongly hydrogen-bond with the hydroxyl groups on the molecular sieve surface, forming a flexible interfacial transition layer between the thermoplastic polymer continuous phase and the molecular sieve particles. Simultaneously, its polymeric segments have good compatibility with the thermoplastic polymer matrix, thus bridging the molecular sieve and the matrix. This interfacial transition layer can effectively absorb interfacial stress when the desiccant product is subjected to bending or compression deformation, reducing interfacial debonding and powder shedding caused by modulus mismatch between the rigid molecular sieve particles and the thermoplastic polymer matrix, thereby preventing powder shedding during installation and under normal use after installation.
[0023] Furthermore, the processing aids include antioxidants and / or lubricants. The antioxidants are preferably hindered phenolic antioxidants (such as antioxidant 1010, antioxidant 1076) or / and phosphite antioxidants (such as antioxidant 168) to prevent thermal oxidative degradation of the polymer matrix during high-temperature processing. The lubricant is at least one of calcium stearate, zinc stearate, magnesium stearate, polyethylene wax, oxidized polyethylene wax, and ethylene bis-stearamide to improve flowability and release properties during melt blending and reduce agglomeration of molecular sieve particles.
[0024] Furthermore, the auxiliary absorbent material is a substance that is solid at 25°C and has an initial thermal decomposition temperature higher than the processing temperature of the selected polymer, and can absorb moisture through physical adsorption, capillary coagulation or chemical bonding.
[0025] In a more preferred embodiment, the auxiliary absorbent material is selected from one or more of natural polysaccharides and their derivatives, synthetic superabsorbent polymers, polyols, and solid sugar alcohols. These substances can continue to absorb moisture through swelling, capillary coagulation, or hydration after rapid adsorption by the molecular sieve, further enhancing their moisture absorption capacity or regulating their moisture absorption characteristics.
[0026] Specifically, the auxiliary absorbent material is selected from one or more of the following categories:
[0027] Natural polysaccharides and their derivatives: microcrystalline cellulose, nanocellulose, cellulose powder, carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, cellulose acetate, cellulose nitrate, starch, pregelatinized starch, oxidized starch, carboxymethyl starch, sodium carboxymethyl starch, hydroxypropyl starch, hydroxyethyl starch, cationic starch, amphoteric starch, dextrin, cyclodextrin, β-cyclodextrin, γ-cyclodextrin, chitosan, carboxymethyl chitosan, sodium alginate, potassium alginate, ammonium alginate, pectin, agar, carrageenan, xanthan gum, guar gum, locust bean gum, gum arabic, konjac glucomannan, sodium hyaluronate, chondroitin sulfate;
[0028] Synthetic superabsorbent polymers: polyacrylic acid, sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, polyacrylamide, poly(acrylic acid-co-acrylamide) copolymer, poly(acrylic acid-co-maleic acid) copolymer, poly(acrylic acid-co-itaconic acid) copolymer, starch-grafted acrylate, cellulose-grafted acrylate, polyvinyl alcohol, polyvinyl butyral, polyethylene oxide (polyethylene glycol), polypropylene glycol, poly(N-vinylpyrrolidone), polyvinyl methyl ether, poly(2-hydroxyethyl methacrylate), poly(N-isopropylacrylamide), polyvinyl sulfonic acid, sodium polystyrene sulfonate, sodium poly(4-styrene sulfonate), poly(acrylic acid-2-acrylamido-2-methylpropanesulfonic acid) copolymer, polyacrylonitrile hydrolysate;
[0029] Polyols and solid sugar alcohols: sorbitol, xylitol, mannitol, maltitol, lactitol, isomaltitol, erythritol.
[0030] In a more preferred embodiment, the auxiliary absorbent material is selected from at least one of sodium polyacrylate, sodium carboxymethyl cellulose, polyethylene oxide, polyvinyl alcohol, sorbitol, sodium alginate, and starch-grafted sodium acrylate.
[0031] In a preferred embodiment, the amount of the auxiliary absorbent material added is 1 to 10 parts by weight.
[0032] In a more preferred embodiment, the amount of the auxiliary absorbent material added is 2 to 5 parts by weight.
[0033] Preferably, the toughened polymer / molecular sieve blend injection molding desiccant is prepared from the following raw materials: 25-40 parts by weight of thermoplastic polymer, 55-68 parts by weight of molecular sieve, 8-20 parts by weight of flexible polymer, 1-3 parts by weight of compatibilizer, 0.5-1 parts by weight of processing aid, and 1-10 parts by weight of auxiliary water-absorbing material.
[0034] The preparation method of the above-mentioned toughened polymer / molecular sieve blend injection molding desiccant adopts a stepwise melt blending and injection molding process, and the specific steps are as follows:
[0035] (1) Dry the thermoplastic polymer granules and flexible polymer granules thoroughly at 80-100℃ respectively;
[0036] (2) First, the flexible polymer and a portion of the thermoplastic polymer are premixed in proportion, and then melt-blended and extruded into granules at 150-280°C using a twin-screw extruder to obtain toughening masterbatch; this step helps the flexible component to be pre-dispersed in the thermoplastic polymer, and promotes the final formation of a uniform and stable dispersed phase structure under the action of the compatibilizer.
[0037] (3) The toughening masterbatch, the remaining thermoplastic polymer, the pre-activated molecular sieve, the compatibilizer, the processing aid, and the optional auxiliary water-absorbing material are added to a high-speed mixer according to the final ratio and premixed evenly; the pre-activation of the molecular sieve is to dry it at 250-450°C for 1-8 hours to make its moisture content less than 2 wt%;
[0038] (4) Add the premix obtained in step (3) into a twin-screw extruder and perform secondary melt blending extrusion at 150-280°C with a screw speed of 200-400 rpm. This allows the molecular sieve to be uniformly dispersed in the continuous phase of the thermoplastic polymer under high shear, while the flexible polymer is uniformly dispersed in the continuous phase under the action of the compatibilizer. The two, together with the molecular sieve, form a stable multiphase composite structure. After extrusion, the material is cooled by water and pelletized to obtain toughened desiccant masterbatch.
[0039] (5) The toughened desiccant masterbatch is injection molded at 160-310°C to obtain desiccant products of a specified shape, including various irregularly shaped components. Extrusion molding can also be used if necessary.
[0040] This invention addresses the problem that introducing a flexible phase into a high-filling system can lead to a sharp increase in melt viscosity and a significant narrowing of the processing window by using a stepwise blending process and precise temperature and shear control.
[0041] The desiccant product has a non-solid flat plate cross-sectional shape, selected from one of the following: inverted trapezoidal, C-shaped, wave-shaped, wedge-shaped, thin rod-shaped, or annular.
[0042] The toughened injection-molded desiccant product after molding has a flexural modulus that is 30% to 70% lower than that of the same thermoplastic polymer / molecular sieve injection molding system without flexible polymers, and an elongation at break of more than 20%, preferably more than 50%. It can produce visible elastic bending and compression deformation under external force, and basically return to its original shape after the external force is removed. It can be repeatedly bent to 90° around a 10mm diameter round bar without surface cracks.
[0043] This invention also claims protection for the application of the aforementioned toughened desiccant as an elastically deformable moisture-absorbing component in various confined spaces. These confined spaces include, but are not limited to, the interiors of battery packs, electronic instrument housings, medical devices, and medicine bottles. In application, the toughened desiccant, injection-molded into a specific cross-sectional shape (such as an inverted trapezoid, C-shape, wave shape, wedge shape, thin rod shape, or ring shape), can be inserted, clipped, or inserted into narrow gaps, grooves, or curved cavities through elastic compression deformation, utilizing the compressible space provided by the cross-sectional shape itself. It relies on elastic recovery force to achieve interference fit, eliminating the need for clips or adhesive backing, making installation convenient and allowing for easy removal and replacement. For medical devices with curved cavities, such as endoscope storage cabinets, the thin rod-shaped desiccant can be pre-deformed along the direction of the tube's curvature before insertion, adapting to the tube's curvature and continuously adhering to the inner wall for moisture absorption. For the inner cavity of medicine bottle caps, annular or wedge-shaped desiccant plugs can be elastically pressed into the pre-drilled groove in the cap, preventing detachment and powder shedding, and ensuring indirect contact with the medicine only through air. Furthermore, this material retains a certain degree of thermoplastic remolding capability, and can also be softened by localized heating, then bonded to complex surfaces and cooled to set, forming a permanent conformal drying layer. The desiccant product does not come into direct contact with human tissue during application; it is only used for air drying inside instruments or containers.
[0044] The present invention also provides a battery pack in which the toughened desiccant described in the present invention is assembled in the shell by means of elastic interference pressing. The toughened desiccant has an inverted trapezoidal or wedge-shaped cross section and is fixed in the gap between the shell and the module or in the reinforcing rib channel by the rebound force after the cross section is elastically compressed.
[0045] The present invention also provides an electronic instrument comprising a housing and a circuit unit located within the housing, characterized in that the inner wall of the housing is fixed with a conformal drying layer formed by the toughened desiccant described in the present invention by means of heating to soften and bonding and cooling to solidify; or a fastener made of the toughened desiccant (flexible desiccant) described in the present invention is assembled inside the housing by means of elastic deformation snapping.
[0046] The present invention also provides a medical device comprising a housing and functional components located within the housing, wherein the toughened desiccant described in the present invention is assembled within the housing or within a conduit by means of elastic deformation pressing, bending insertion, or heating softening and cooling shaping.
[0047] The present invention also provides a medicine bottle, comprising a bottle body and a bottle cap, wherein a moisture-absorbing plug or moisture-absorbing ring made of the toughened desiccant described in the present invention is assembled in the inner cavity of the bottle cap or the inner cavity of the bottle body by means of elastic deformation pressing or snapping.
[0048] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0049] (1) The toughened desiccant product of the present invention has a flexural modulus that is 30% to 70% lower than that of the same thermoplastic polymer / molecular sieve injection molding system without flexible polymer, and a breaking elongation greater than 20%. It can produce visible elastic bending and compression deformation under external force, and basically recovers its original shape after the external force is removed. It can be repeatedly bent to 90° around a round rod with a diameter of 10 mm without cracks appearing on the surface.
[0050] (2) The toughened desiccant product of the present invention can achieve a saturated moisture absorption rate of more than 15% of its own weight in 28 days at 23°C and 90% relative humidity.
[0051] (3) By introducing a flexible polymer and using the bridging effect of a compatibilizer to uniformly disperse it in the continuous phase of a thermoplastic polymer, this invention successfully prepared a toughened desiccant structural component that combines injection molding precision, sufficient strength and moderate elasticity. It can be fixed by interference fit through the elastic compression deformation of the cross-sectional shape, and is especially suitable for irregular and confined spaces inside battery packs, electronic instruments, medical devices, medicine bottles and other similar devices. Attached Figure Description
[0052] Figure 1 This is a schematic diagram of the toughened injection-molded drying sheet prepared in Embodiment 1 of the present invention being elastically pressed into the reinforcing rib groove of the battery pack housing.
[0053] Figure 2 This is a schematic diagram of the toughened injection-molded drying strip (flexible drying sheet) prepared in Embodiment 3 of the present invention placed in a reagent test kit (below the white test paper).
[0054] Figure 3 The images show rectangular toughened injection-molded drying sheets (flexible drying sheets) of different thicknesses obtained in Example 5 of this invention.
[0055] Figure 4 This is a photograph of the sheet-like ultrathin dried sheet obtained in Example 6 of the present invention (which can be applied to the inside of the packaging film).
[0056] Figure 5 The image shown is a scanning electron microscope (SEM) image of the cross-section of the toughened injection-molded drying sheet prepared in Example 5 of the present invention. It can be seen that the fine particles of the molecular sieve are uniformly distributed in the matrix. Detailed Implementation
[0057] The present invention will be further described in detail below with reference to embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto. All raw materials involved in the present invention can be purchased directly from the market. For process parameters not specifically specified, conventional techniques can be referred to.
[0058] In all embodiments, moisture absorption tests were conducted at 23°C and 90% relative humidity, measuring the percentage weight gain after 28 days of saturation. Thermogravimetric analysis (TGA) was performed under a nitrogen atmosphere at a heating rate of 10°C / min. Flexural modulus was tested according to ISO 178, and elongation at break was tested according to ISO 527.
[0059] Example 1
[0060] Take 13X type molecular sieve (pore size approximately 1 nm, particle size D = 5 μm, specific surface area ≥ 550 m²). 2 (g) was activated at 350℃ for 3 hours and then cooled to room temperature.
[0061] By weight, take 35 parts homopolymer polypropylene (melt index 3g / 10min, 230℃ / 2.16kg), 63 parts activated molecular sieve, 15 parts SEBS (styrene content 30%), 2 parts maleic anhydride grafted SEBS (grafting rate 1.0%), 0.2 parts antioxidant 1010, and 0.5 parts calcium stearate.
[0062] First, SEBS is premixed with 10 parts of PP and then extruded and granulated at 170-200℃ using a twin-screw extruder to obtain toughening masterbatch. Then, the toughening masterbatch is premixed evenly with the remaining 25 parts of PP, all molecular sieves, compatibilizer and processing aids in a high-speed mixer to obtain premixed material.
[0063] The premixed material was added to a co-rotating twin-screw extruder, with the temperatures of each section set to 165℃, 185℃, 200℃, 205℃, and 200℃, and the screw speed set to 300 rpm. The material was melt-blended and extruded into granules. The resulting particles were injection molded at 195℃ into rectangular dry sheets (20 mm long, 14 mm wide, and 3 mm thick).
[0064] The dried strip is hard and tough to the touch. It can be bent more than 30° along its length without breaking, and it will return to its original shape without cracking after being released. The flexural modulus is about 820MPa (the flexural modulus of the pure PP / molecular sieve injection molding system with the same filling amount is 2100MPa, a reduction of 61.0%), and the elongation at break is 68%. In an environment of 23℃ and 90%RH, the saturated moisture absorption rate reaches 18.2% after 28 days.
[0065] The desiccant sheet was pressed into a groove only 5mm thick at the bottom of the battery pack casing, where it was firmly fitted by the rebound force after the cross-section was compressed elastically, and it did not loosen during vibration testing. In a simulated high humidity (90%RH) environment, the humidity inside the tube remained below 30%RH after 4 hours.
[0066] Example 2
[0067] By weight, 30 parts copolymer PP (ethylene content approximately 8%), 68 parts 13X molecular sieve powder (average particle size 3 μm), 10 parts polyester-type TPU (Shore A85), 15 parts POE (octene content 40%), 2 parts maleic anhydride-grafted POE (grafting rate 1.0%), 0.3 parts antioxidant 168, and 0.4 parts zinc stearate were taken. The molecular sieve was activated according to the method in Example 1.
[0068] First, TPU and POE are premixed with 15 parts of PP to obtain a toughening masterbatch. The toughening masterbatch is then blended with the remaining 15 parts of PP, molecular sieve, compatibilizer, and processing aids to obtain a premix. The premix is then subjected to secondary melt-blending extrusion granulation using a twin-screw extruder at an extrusion temperature of 170–210°C and a screw speed of 280 rpm. The resulting granules are then injection molded at 200°C into C-shaped fasteners with openings (outer diameter 25 mm, wall thickness 3 mm, opening width 5 mm). This fastener can be easily opened by hand to 8 mm and elastically clamped onto the cylindrical conduit (diameter 6 mm) of a portable medical diagnostic instrument, relying on its elastic recovery force for a secure fit.
[0069] Performance testing: flexural modulus approximately 750 MPa, elongation at break 95%, 28-day saturated moisture absorption rate 19.5%. During post-installation testing, the humidity inside the pipe was consistently maintained below 35% RH.
[0070] Example 3
[0071] By weight, 32 parts homopolymer polypropylene (melt index 12 g / 10 min), 62 parts 13X molecular sieve powder (average particle size 8 μm), 8 parts SEBS (styrene content 30%), 3 parts silane coupling agent KH-550, 0.3 parts antioxidant 1010, 0.4 parts polyethylene wax, and 2 parts auxiliary water-absorbing material sodium carboxymethyl cellulose (degree of substitution 0.7, TGA shows thermal decomposition temperature > 260℃). The 13X molecular sieve was activated at 400℃ for 3 hours and then cooled to room temperature to obtain activated molecular sieve.
[0072] The stepwise blending process of Example 1 (first, SEBS and 10 parts of PP are premixed to obtain toughening masterbatch, and then blended with the remaining 22 parts of PP, molecular sieve, compatibilizer, processing aid and auxiliary water-absorbing material) is used to prepare granules. The granules are injection molded at 195°C into rectangular cross-section drying strips (15 mm long, 3 mm wide and 1.8 mm thick).
[0073] The wedge-shaped strip cross-section can be elastically compressed to approximately 1.5 mm along the thickness direction, with a flexural modulus of approximately 1150 MPa and an elongation at break of 38%; its 28-day saturated moisture absorption rate is 18.3%. When pressed into the elongated gap between the reagent test kit module end plate and the shell, its elastic rebound force securely locks it in place. It can be pried out with a tool during disassembly.
[0074] Example 4
[0075] By weight, 30 parts copolymer PP, 60 parts 4A molecular sieve powder (average particle size 2μm), 20 parts POE (octene content 38%, melt index 1g / 10min), 2 parts maleic anhydride-grafted PP (grafting rate 1.2%), 0.3 parts antioxidant 1010, 0.5 parts calcium stearate, and 5 parts auxiliary water-absorbing material starch-grafted sodium acrylate (SAP, TGA thermal decomposition temperature >280℃) were taken. The 4A molecular sieve was activated at 450℃ for 5 hours and cooled to room temperature to obtain activated molecular sieve.
[0076] POE was first premixed with 15 parts of PP to obtain a toughening masterbatch. The toughening masterbatch was then blended with the remaining 15 parts of PP, molecular sieve, compatibilizer, processing aid, and SAP to obtain a premix. The premix was then subjected to secondary melt-blending extrusion granulation using a twin-screw extruder at an extrusion temperature of 170–210°C and a screw speed of 320 rpm. The resulting granules were injection molded into thin rod-shaped dried parts (4 mm in diameter and 50 mm in length) at 200°C.
[0077] This thin rod can be repeatedly bent up to 180° around a 15mm diameter circular shaft without cracking, with a flexural modulus of approximately 680MPa and an elongation at break of 125%; its 28-day saturated moisture absorption rate is 22.1%. It is used in the annular drying chamber (3mm wide, approximately 20mm bending radius) of a portable blood glucose meter test strip compartment. The thin rod is fed into the chamber while bending along it, relying on its own elasticity to adhere to the chamber wall.
[0078] Example 5
[0079] By weight, 35 parts homopolymer polypropylene (melt index 8 g / 10 min), 58 parts 5A molecular sieve powder (average particle size 10 μm), 12 parts linear SBS (styrene / butadiene ratio 30 / 70), 1.5 parts maleic anhydride-grafted SEBS (grafting rate 1.5%), 0.2 parts antioxidant 168, 0.3 parts ethylene bis-stearamide, and 3 parts auxiliary water-absorbing material sorbitol (powder, TGA showed weight loss <1% before 240℃). The 5A molecular sieve was activated at 400℃ for 3 hours and cooled to room temperature to obtain activated molecular sieve.
[0080] First, SBS and 12 parts of PP are premixed to obtain toughening masterbatch. The toughening masterbatch is then blended with the remaining 23 parts of PP, molecular sieve, compatibilizer, processing aid, and sorbitol to obtain premix. The premix is then subjected to secondary melt blending extrusion granulation through a twin-screw extruder at an extrusion temperature of 160-210℃ and a screw speed of 280 rpm. The resulting granules are then injection molded into rectangular dry sheets of different thicknesses.
[0081] This desiccant sheet can be easily compressed along its cross-sectional height, with a flexural modulus of approximately 700 MPa and an elongation at break of 88%; its 28-day saturated moisture absorption rate is 20.5%. Used in irregular heat dissipation slots within the housings of electronic instruments in outdoor communication base stations, the desiccant sheet can be cut to fit the desired internal shape and attached to the interior.
[0082] Example 6
[0083] By weight, 28 parts homopolymer PP, 60 parts 4A molecular sieve powder (average particle size 3 μm), 18 parts polyester-type TPU (Shore A90), 2 parts maleic anhydride-grafted PE (grafting rate 0.8%), 0.3 parts antioxidant 1010, 0.4 parts magnesium stearate, and 5 parts auxiliary absorbent material sodium polyacrylate (crosslinked type, TGA shows thermal decomposition temperature > 280℃) were taken. The molecular sieve was activated according to the method in Example 4.
[0084] First, TPU and 15 parts of PP are premixed to obtain toughening masterbatch. The toughening masterbatch is then blended with the remaining 13 parts of PP, molecular sieve, compatibilizer, processing aid, and sodium polyacrylate to obtain premix. The premix is then subjected to secondary melt blending and extrusion granulation through a twin-screw extruder, and then melt extruded at 200°C through a single-screw extruder with a coat hanger die. The film is then stretched by a three-roll calender to obtain a continuous ultra-thin moisture-absorbing film with a thickness of 0.2 mm.
[0085] This desiccant sheet is extremely flexible, can be folded in half without breaking, has a flexural modulus of approximately 620 MPa, and an elongation at break exceeding 200%; its 28-day saturated moisture absorption rate is 20.5%. It can be used inside the packaging bags of medical devices (attached to the inside).
[0086] Example 7
[0087] By weight, 40 parts copolymer PP, 55 parts 5A molecular sieve powder (average particle size 6 μm), 10 parts SEBS (styrene content 33%), 1 part maleic anhydride-grafted POE (grafting rate 1.2%), 0.2 parts antioxidant 1010, and 0.3 parts polyethylene wax were taken. The molecular sieve was activated according to the method in Example 5.
[0088] After all materials are premixed, they are extruded and granulated by a twin-screw extruder at 170-210°C. The resulting granules are then injection molded into C-shaped buckles (20mm inner diameter, 4mm opening) by an injection molding machine at a barrel temperature of 190-210°C and a mold temperature of 50°C.
[0089] The buckle has a flexural modulus of approximately 1020 MPa, an elongation at break of 30%, and a 28-day saturated moisture absorption rate of 17.0%. Its dispersion uniformity is slightly worse than that of stepwise blending, but it still meets the requirement of no powder shedding, demonstrating process flexibility.
[0090] Example 8
[0091] By weight, 33 parts homopolymer PP, 60 parts 3A / 4A mixed molecular sieve (mass ratio 1:1, average particle size 5μm), 12 parts POE (octene content 44%), 1.5 parts maleic anhydride-grafted PP (grafting rate 1.5%), 0.3 parts antioxidant 168, 0.4 parts calcium stearate, and 4 parts sodium alginate (TGA shows thermal decomposition temperature >250℃) were used as auxiliary water-absorbing material. The molecular sieve was activated at 400℃ for 4 hours and then cooled to room temperature to obtain activated molecular sieve.
[0092] A step-by-step blending process was used to injection mold an annular desiccant with a wedge-shaped surface (outer diameter 22mm, inner diameter 14mm, height 8mm, with three annular ribs on the outer wall) at 190℃.
[0093] This desiccant is used for interference fitting inside the bottle cap of a pharmaceutical vial, requiring a force of over 15N to remove; its flexural modulus is approximately 780MPa, its elongation at break is 72%, and its 28-day saturated moisture absorption rate is 21.8%. In accelerated stability tests of pharmaceuticals, the humidity inside the vial was maintained below 20%RH, with no powder shedding or deformation.
[0094] Example 9
[0095] By weight, 35 parts homopolymer PP, 60 parts 13X molecular sieve powder (average particle size 8 μm), 10 parts SEPS (styrene content 25%), 2 parts titanate coupling agent, 0.3 parts antioxidant 1010, 0.5 parts zinc stearate, and 3 parts auxiliary water-absorbing material polyethylene oxide (TGA shows weight loss <2% at 210°C) were taken. The molecular sieve was activated according to the method in Example 1.
[0096] Using the process described in Example 1, a flexible drying clip was injection molded and clamped onto the outer wall of a medical catheter. The drying clip has a flexural modulus of approximately 890 MPa, an elongation at break of 55%, and a 28-day saturated moisture absorption rate of 19.8%.
[0097] Example 10
[0098] By weight, 30 parts of polyamide 6 (PA6), 58 parts of 4A molecular sieve powder (average particle size 3 μm), 15 parts of TPU (polyether type, Shore A88), 2 parts of maleic anhydride-grafted POE (grafting rate 1.5%), 0.3 parts of antioxidant 1098, 0.4 parts of calcium stearate, and 5 parts of polyvinyl alcohol (TGA initial decomposition temperature approximately 250℃) were used as auxiliary water-absorbing material. The 4A molecular sieve was activated at 400℃ for 6 hours and then cooled to room temperature to obtain activated molecular sieve.
[0099] Using a step-by-step blending process (extrusion temperature 230~260℃, injection molding temperature 260~275℃), a drying bracket with elastic claws is injection molded for moisture-proof fixation of PCB boards inside electronic instruments.
[0100] The flexural modulus of the support is approximately 980 MPa, the elongation at break is 42%, and the 28-day saturated moisture absorption rate is 20.6%.
[0101] Example 11 (Comparison of the effects of compatibilizers and auxiliary absorbent materials)
[0102] This example compares the effects of adding compatibilizers and auxiliary absorbent materials. The basic formulation (Formula B) consists of 35 parts PP, 60 parts 13X molecular sieve (D=5μm), 10 parts SBS, 0.3 parts antioxidant, and 0.4 parts calcium stearate. The molecular sieve was activated according to the method in Example 1. Compatibilizers and / or auxiliary absorbent materials were added to this basic formulation, as shown in Table 1.
[0103] Table 1
[0104]
[0105] All formulations were extruded, granulated, and injection molded into long strips using the stepwise blending process described in Example 1. Each corrugated strip underwent a bending cycle test: repeatedly bent 90° around a 10mm diameter round rod, with the surface observed and weighed every 10 bends. Formulation B (without compatibilizer) showed trace amounts of powder shedding after 50 bends, with a cumulative weight loss of 0.28% after 100 bends; while Formulation A (containing PP-g-MAH) remained smooth after 100 bends, with no visible powder shedding, and a cumulative weight loss of only 0.05%. Formulations C and D maintained excellent anti-powdering properties while significantly increasing moisture absorption to over 20%. SEM observation showed that the molecular sieve interface with the PP matrix was blurred and tightly bonded in the compatibilizer-containing formulation, while localized interfacial gaps were visible in the compatibilizer-free formulation. This embodiment demonstrates that adding a compatibilizer can significantly improve the desiccant's durability against powder shedding during repeated elastic deformation without sacrificing its moisture absorption capacity, while the addition of an auxiliary absorbent material can further enhance its moisture absorption capacity.
[0106] Comparative Example 1
[0107] Based on Example 1, the polypropylene was increased to 55 parts, the molecular sieve was reduced to 40 parts (less than 50 parts), and no flexible polymers or compatibilizers were added. The remaining processing conditions were the same as in Example 1. The resulting product had a saturated moisture absorption rate of only 8.2% after 28 days at RH 90%; severe powdering occurred on the surface when bent, and the elongation at break was only 3.5%, making it impossible to achieve elastic deformation installation.
[0108] Comparative Example 2
[0109] Using the exact same formulation as Example 1 (35 parts PP, 63 parts molecular sieve, 15 parts SEBS, 2 parts PP-g-MAH, 0.2 parts antioxidant, 0.5 parts calcium stearate), 2mm sheets were prepared solely through melt blending followed by hot pressing (190°C, 10MPa), without injection molding flow orientation. The sheet exhibited a saturated moisture absorption rate of 11.5% after 28 days at RH 90%, but its mechanical strength was poor, making it difficult to form thin-walled mesh structures and elastic snaps; microcracks appeared after bending.
[0110] Application Example 1 (The toughened desiccant sheet prepared in Example 1 is used for dehumidification inside the power battery pack of new energy vehicles)
[0111] The rectangular toughened drying sheet (20mm long, 14mm wide, and 3mm thick) prepared in Example 1 was elastically compressed and deformed into the reinforcing groove (5mm wide) at the bottom of the power battery pack housing for new energy vehicles. During insertion, the drying sheet experienced approximately 0.5mm of elastic compression along its width, and its elastic restoring force formed an interference fit with the side walls of the groove, firmly embedding it within the groove. In a simulated vehicle vibration test (vibration frequency 10–55Hz, amplitude 3mm, duration 8 hours), the drying sheet showed no loosening or displacement, and no powder shedding from its surface. A battery pack equipped with the drying sheet was placed in a 40°C, 95%RH environment for a 168-hour condensation simulation test. The relative humidity inside the battery pack remained below 25%, and the insulation resistance between modules was >100MΩ, meeting electrical safety requirements. In contrast, the humidity inside the control group battery pack without the drying sheet exceeded 70% after 48 hours, and obvious condensation appeared on the module surface. Furthermore, after the desiccant becomes saturated with moisture, it can be desorbed and regenerated by heating in an 80°C oven for 12 hours. After being reused three times, its saturated moisture absorption rate can still remain above 85% of the initial value. This application example demonstrates that the toughened desiccant prepared in Example 1 possesses the dual advantages of "flexible compression installation" and "high moisture absorption capacity," making it suitable for dehumidification scenarios in enclosed cavities with stringent requirements for insulation safety and space utilization, such as power battery packs and energy storage systems for new energy vehicles.
[0112] Application Example 2 (The C-shaped snap-fit toughened desiccant prepared in Example 2 is used for moisture protection of the internal conduit of portable medical devices)
[0113] The C-shaped clip (outer diameter 25mm, wall thickness 3mm, opening width 5mm) prepared in Example 2 was manually opened to approximately 8mm and elastically clamped onto the cylindrical tubing (diameter 6mm) inside the portable continuous glucose meter. The C-shaped clip, relying on its elastic restoring force, forms a 360° circumferential grip with the outer wall of the tubing, requiring no adhesive backing or screws for fixation. The installation process can be completed within 3 seconds, and disassembly is simple; just open the clip to remove the meter, facilitating device maintenance and desiccant replacement. The glucose meter was placed in a constant temperature and humidity chamber (37℃, 85%RH) simulating a human wearing environment and operated continuously for 7 days. Throughout the testing period, the C-shaped clip remained firmly attached to the outer wall of the tubing without slippage or rotation, and no dust fell from the surface. The internal humidity of the instrument remained below 30%RH, and the electrochemical sensor signal output was stable, with no measurement deviation caused by humidity drift. This application example demonstrates that the C-shaped snap-fit toughened desiccant prepared in Example 2, with its unique open elastic clamping structure, can achieve rapid and non-destructive installation without changing the original assembly process of medical devices. It is especially suitable for internal moisture-proofing applications such as portable diagnostic instruments and wearable medical devices that have stringent requirements for ease of assembly, cleanliness, and reliability.
[0114] Application Example 3 (Extrusion film forming for preparing ultra-thin moisture-absorbing films for use as inner liners in pharmaceutical blister packaging)
[0115] The toughened desiccant masterbatch obtained in Example 6 was melt-extruded at 200°C using a single-screw extruder with a coat hanger-type die. The resulting film was then stretched using a three-roll calender to produce a continuous ultra-thin moisture-absorbing film with a thickness of 0.15–0.30 mm. The film was cut to a size suitable for the aluminum foil substrate of the pharmaceutical blister packaging and then bonded to the inside of the aluminum foil of the blister packaging via hot-pressing (without direct contact with the drug, communicating only with the drug's chamber through micropores in the aluminum foil or air inside the packaging), thus creating an integrated drying blister package. Accelerated stability tests (6 months) were conducted on amoxicillin capsules at 25°C and 75%RH. The relative humidity inside the blister packaging using this moisture-absorbing film remained below 25%, while the relative humidity inside the control group blister packaging without the desiccant film rose to over 60%, and the capsule contents showed significant deliquescence and clumping. This application example demonstrates that ultra-thin, flexible, continuous moisture-absorbing films can be mass-produced using an extrusion film forming process. These films can serve as integrated drying liners for pharmaceutical blister packaging, achieving effective protection for moisture-sensitive solid pharmaceuticals with almost no increase in packaging thickness.
[0116] Practical Example 4 (Extrusion film forming to prepare cuttable moisture-absorbing sheets for use as inner liners for precision electronic component trays)
[0117] The toughened desiccant masterbatch obtained in Example 6 was used in the above-described extrusion film forming process. The traction roller speed was adjusted to control the film thickness to 0.20–0.40 mm, resulting in a continuous moisture-absorbing sheet with a width of 300 mm. This sheet can be stored for a long time and can be cut into any size and shape as needed. Taking the smartphone motherboard surface mount production process as an example, the cut moisture-absorbing sheet is placed at the bottom of an IC chip carrier tray. During the stacking and transportation of chips within the tray, the sheet adheres to the uneven surface of the tray bottom due to its slight elastic deformation, achieving positioning without adhesive or clips. Simulating chip storage for 72 hours in a high-humidity environment of 30°C and 85%RH, the relative humidity inside the tray with the moisture-absorbing sheet remained below 40%, with no condensation on the chip surface and no oxidation or discoloration of the leads. In contrast, the humidity inside the control group tray without the moisture-absorbing sheet was close to the ambient humidity (approximately 80%RH), and some chip leads showed slight oxidation spots. After absorbing moisture, the absorbent sheet can be desorbed and regenerated by heating in an 80°C oven for 2 hours. After being reused 5 times, the saturated moisture absorption rate still remains above 90% of the initial value. This application example shows that the cuttable absorbent sheet prepared by the extrusion film forming process can serve as a convenient, flexible, and recyclable solution for localized environmental humidity control in the manufacturing and turnover of electronic components. It is especially suitable for pallet packaging protection of high-value chips, sensors, optical lenses, and other precision components with stringent requirements for humidity and cleanliness.
[0118] As can be seen from the above embodiments and comparative examples, this invention successfully prepares a toughened desiccant that combines injection molding precision, sufficient strength, and moderate elasticity by using a stepwise melt blending injection molding process with a thermoplastic polymer as the continuous phase and a flexible polymer uniformly dispersed therein under the action of a compatibilizer. The desiccant is further enhanced by adding a compatibilizer to strengthen the interface, processing aids to improve processability, and optional auxiliary absorbent materials to increase moisture absorption capacity. It exhibits excellent elastic compression installation, bending insertion, and conformal fixing capabilities in confined spaces such as battery packs, electronic instruments, medical devices, and medicine bottles. This solves the engineering problems of rigid injection molded parts being unable to adapt to irregular gaps and the low strength and poor shape retention of purely flexible parts, and has broad application prospects in new energy, medical health, and pharmaceutical packaging fields.
[0119] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A toughened polymer / molecular sieve blend injection molding desiccant, characterized in that, The raw materials for its preparation include the following components: 20-45 parts by weight of thermoplastic polymer, 50-78 parts by weight of molecular sieve, 5-25 parts by weight of flexible polymer, 0.5-5 parts by weight of compatibilizer, 0.2-3 parts by weight of processing aid, and 0.5-25 parts by weight of auxiliary water-absorbing material; the particle size D of the molecular sieve is 1-10 μm. The weight ratio of the thermoplastic polymer to the flexible polymer is (50-90):(10-50); the thermoplastic polymer is selected from at least one of polyolefin, polyamide, thermoplastic polyurethane, polycarbonate, and polyoxymethylene; the flexible polymer is selected from at least one of styrene-based block copolymer, polyolefin elastomer, and thermoplastic polyurethane elastomer; the thermoplastic polymer forms a continuous phase matrix, and the flexible polymer is uniformly dispersed in the continuous phase under the action of a compatibilizer.
2. The toughened polymer / molecular sieve blend injection molding desiccant according to claim 1, characterized in that, The polyolefin is at least one of polypropylene, high-density polyethylene, low-density polyethylene, linear low-density polyethylene, ethylene-vinyl acetate copolymer, and ethylene-ethyl acrylate copolymer; the polyamide is at least one of polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, and polyamide 1010. The styrene-based block copolymer is at least one of styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated styrene-isoprene-styrene block copolymer, styrene-ethylene-ethylene-propylene-styrene block copolymer, and styrene-isobutylene-styrene block copolymer.
3. The toughened polymer / molecular sieve blend injection molding desiccant according to claim 1, characterized in that, The weight ratio of the thermoplastic polymer to the flexible polymer is (60-80):(20-40).
4. The toughened polymer / molecular sieve blend injection molding desiccant according to claim 1, characterized in that, The molecular sieve is selected from at least one of 3A, 4A, 5A, 13X, Y-type, and ZSM-5 type molecular sieves, with a specific surface area ≥ 500 m². 2 / g, pore size 0.3~1.2 nm, particle size D is 1~8 μm.
5. The toughened polymer / molecular sieve blend injection molding desiccant according to claim 1, characterized in that, The compatibilizer is at least one of maleic anhydride-grafted polypropylene, maleic anhydride-grafted polyethylene, maleic anhydride-grafted SEBS, maleic anhydride-grafted POE, silane coupling agent, titanate coupling agent, and aluminate coupling agent.
6. The toughened polymer / molecular sieve blend injection molding desiccant according to claim 1, characterized in that, The processing aids include antioxidants and / or lubricants, wherein the antioxidants are hindered phenolic antioxidants and / or phosphite antioxidants; and the lubricants are at least one of calcium stearate, zinc stearate, magnesium stearate, polyethylene wax, oxidized polyethylene wax, and ethylene bis-stearamide. The auxiliary absorbent material is selected from one or more of the following: natural polysaccharides and their derivatives, synthetic superabsorbent polymers, polyols, and solid sugar alcohols.
7. A method for preparing the toughened polymer / molecular sieve blend injection molding desiccant according to any one of claims 1-6, characterized in that, The specific steps are as follows: (1) Dry the thermoplastic polymer granules and flexible polymer granules thoroughly at 80-100℃ respectively; (2) First, the flexible polymer and a portion of the thermoplastic polymer are premixed in proportion, and then melt-blended and extruded into granules at 150-280°C using a twin-screw extruder to obtain toughening masterbatch; (3) The toughening masterbatch, the remaining thermoplastic polymer, the pre-activated molecular sieve, the compatibilizer, the processing aid, and the optional auxiliary water-absorbing material are added to a high-speed mixer according to the final ratio and premixed evenly; the pre-activation of the molecular sieve is to dry it at 250-450°C for 1-8 hours to make its moisture content less than 2 wt%; (4) Add the premix obtained in step (3) into a twin-screw extruder and perform secondary melt blending extrusion at 150-280°C with a screw speed of 200-400 rpm. After extrusion, the material is cooled by water and pelletized to obtain toughened desiccant masterbatch. (5) The toughened desiccant masterbatch is injection molded or extruded at 160-310°C to obtain a desiccant product of a specified shape.
8. The preparation method according to claim 7, characterized in that, In the desiccant product, a thermoplastic polymer forms a continuous phase matrix, and a flexible polymer is uniformly blended and distributed in the continuous phase under the action of a compatibilizer; the desiccant product has a non-solid flat plate cross-sectional shape, selected from one of the following: inverted trapezoid, C-shape, wave shape, wedge shape, thin rod shape, or ring shape.
9. The application of the toughened polymer / molecular sieve blend injection molding desiccant according to any one of claims 1-6 as an elastically deformable moisture-absorbing component in various confined spaces.
10. The application according to claim 9, characterized in that, The confined space includes the inside of a battery pack, the inside of an electronic instrument housing, the inside of a medical device, or the inside of a medicine bottle.
Citation Information
Patent Citations
Macromolecule radical hygroscopic material and preparing method thereof
CN101229508B
Travel control apparatus for industrial vehicle
CN101229808A
Melted electrostatic spinning polymer / molecular sieve blended composite fiber as well as preparation method and application thereof
CN120591909A